Middle ear innovation in Early Cretaceous eutherian mammals - Wang, Haibing; Wang, Yuanqing (Nature communications, 2023)
The middle ear ossicles in modern mammals are repurposed from postdentary bones in non-mammalian cynodonts. Recent discoveries by palaeontological and embryonic studies have developed different models for the middle ear evolution in mammaliaforms. However, little is known about the evolutionary scenario of the middle ear in early therians. Here we report a detached middle ear preserved in a new eutherian mammal from the Early Cretaceous Jehol Biota. The well-preserved articulation of the malleus and incus suggest that the saddle-shaped incudomallear joint is a major apomorphy of Early Cretaceous eutherians. By contrast to the distinct saddle-like incudomallear articulation in therians, differences between the overlapping versus the half-overlapping incudomallear joints in monotremes and stem mammals would be relatively minor. The middle ear belongs to the microtype by definition, indicating its adaptation to high-frequency hearing. Current evidence indicates that significant evolutionary innovations of the middle ear in modern therians evolved in Early Cretaceous. The evolution of the middle ear in early therians is unclear. Here, the authors report a reconstructed, detached middle ear in a eutherian mammal from the Early Cretaceous Jehol Biota, suggesting independent decoupling of hearing and chewing apparatuses.